(untitled) (Heritage, 2021)
With the retreat of the Serbian army towards Albania and Corfu, at the end of 1915 the territory of the Kingdom of Serbia was occupied by the forces of the Central Powers. In the division of the occupation plunder, the areas of southeastern Serbia and Vardar Macedonia belonged to the Kingdom of Bulgaria. During the three-year reign over the conquered areas, the Bulgarian occupation troops committed countless crimes. The small town of Surdulica became a symbol of the suffering of the occupied south of Serbia in the Great War, the place where mass crimes had been committed against the civilian population. After the liberation of Serbia in 1918, the citizens of this town launched an initiative to build a memorial ossuary in which the remains of the killed civilians would be buried. The subject of interest of our work is the reporting of the print media on the laying of the foundation-stone for the construction of the Surdulica Memorial Ossuary in 1922. At the same time, we analyzed the details of the newspaper articles about the suffering of the civilian population in Surdulica during the Great War (1915-1918) and the fate of the remains of numerous victims.